Nutritional Evaluation of Edible Non-Timber Forest Produces - a Case Study in South-West Bengal - Das, Nilanjana; Chattopadhyay, R. N. (Indian Forester, 2001)
Non-Timber Forest Products (NTFP) constitute an important source of food for economically backward communities living in the forests of the Nayagram Range of West Midnapore Forest Division , South-West Bengal. Items collected for household consumption include leaves and young shoots , flowers , fruits , tubers , mushrooms etc. The average annual collection was found to be highest for Mahua flowers followed by tubers , leafy vegetables , mushrooms and fruits. The consumption pattern of forest edibles varied widely over the FPCs studied. The present study on nutritional aspect confirms the presence of major nutritive elements in forest edibles in appreciable amount. Therefore , NTFPs have immense prospects to provide solution to the problems of hunger , malnutrition and poverty of the rural poor in the world.